Viral co-detection of influenza virus and other respiratory viruses in hospitalized Brazilian patients during the first three years of the coronavirus disease (COVID)-19 pandemic: an epidemiological profile - Siqueira, Bianca Aparecida; Bredariol, Ketlyn Oliveira; Boschiero, Matheus Negri; Marson, Fernando Augusto Lima (Frontiers in Microbiology, 2024)
The data used to perform the study will be available upon request to the corresponding researcher and are also available on the Brazilian government platform called Open-Data-SUS (https://opendatasus.saude.gov.br/).The study was carried out according to the Declaration of Helsinki and was approved by the Institution's Ethics Committee (Certificate of Presentation for Ethical Appreciation No. 67241323.0.0000.5514; Study approval No. 5.908.611).performed the statistical analysis. [BAS, KOB, MNB, FALM] performed the interpretation of the study findings.[BAS, MNB, FALM] wrote the text and reviewed it carefully before submitting the article to the scientific journal.